1993
DOI: 10.1161/01.str.24.9.1360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-intensity warfarin anticoagulation on level of activity of the hemostatic system in patients with atrial fibrillation. BAATAF Investigators.

Abstract: The Boston Area Anticoagulation Trial for Atrial Fibrillation (BAATAF) demonstrated that low-intensity warfarin anticoagulation can, with safety, sharply reduce the rate of stroke in patients with nonvalvular atrial fibrillation. The beneficial effect of warfarin was presumably related to a decrease in clot formation in the cardiac atria and subsequent embolization. To assess the effect of warfarin therapy on in vivo clotting in patients in the BAATAF, we measured the plasma level of prothrombin acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 24 publications
2
26
0
3
Order By: Relevance
“…Sherman et al [17] found that patients with the greatest risk of embolism were those with hypertension on the basis of their AF. Large, prospective studies [3,18,19] have shown that the risk for thromboembolism does not differ between patients with paroxysmal AF and those with chronic AF. Advanced age and AF in the absence of anticoagulation were the factors that were independently associated with stroke occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Sherman et al [17] found that patients with the greatest risk of embolism were those with hypertension on the basis of their AF. Large, prospective studies [3,18,19] have shown that the risk for thromboembolism does not differ between patients with paroxysmal AF and those with chronic AF. Advanced age and AF in the absence of anticoagulation were the factors that were independently associated with stroke occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In addition, oral anticoagulants suppress thrombin generation with a significant reduction in F1+2. 21,22 Although it has been suggested that among patients with a hypercoagulable state, higher levels of F1+2 could identify a subgroup of patients with higher risk of thrombosis, this observation remains to be proven. Therefore, although we documented an increase in F1+2 and TAT levels in patients receiving G-CSF, the clinical significance of this finding remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…it is expected that there will be a higher mean FI + 2 value in WARSS patients who have recurrent stroke, thus providing a hematologic marker of stroke risk. Based on the findings in the Boston Area Anticoagulation Trial for Atrial Fibrillation study [50], a lower mean FI + 2 level is expected in the coumadin-trcatcd patients as com pared to those on aspirin. The secondary' aim s of HAS are to analyze the natural history of FI + 2 levels over time, correlate these values with data obtained in APASS and PICSS, and correlate FI + 2 values with other vascular risk factors.…”
Section: The Hem Ostatic Syste M Activation Stu D Y (Has)mentioning
confidence: 99%